Characteristics of the Thakhet - Sepon active fault zone - Thom, Bui Van; Hung, Nguyen Van; Sunlinthone, Oneta; Duangpaseuth, Somsanith; Markvilay, Bounpaphan (Vietnam Journal of Earth Sciences, 2015)
Thakhet - Sepon active fault zone is one of  fault zones of the Lao PDR in particular, and  of Indochina block, in general. This fault zone was longer than 550km, extending into Vietnam with nearly 80km in length and with a name Dakrong - Hue. In Laos fault zone consists of three major faults, running nearly parallel in direction NW-SE. During the neotectonic stage it operate under two main phases: the early phase (Late Miocene - early Pliocene) - with left-lateral slip; the late phase (Late Pliocene-Quaternary)- with right-lateral slip. The largest amplitude of the left-lateral slip in the Pleistocen reach 2880m and the rate approximately 9.6 mm / year; the vertical displacement amplitude of about 400m with a rate approximately 1.33 mm/year.Related to fault zones were instrumentally recored earthquakes with 5<Ms<6. Thakhet-Sepon zone can generate earthquakes Msmax³ 6.5.ReferencesDonald L. Wells and Kevin J.Copersmith,1994: New Empirical Relationships among Magnitude, Rupture Length, Rupture Width, Rupture Area, and Surface Displacement. Bl.of SSA. Vol.84, No4, pp 974-1002. Santi Pailoplee, Yuichi Sugiyanna, Punya Charusin, 2010: Deterministic and probabilistic seismic hazard analyses in Thailand and adjust areas using fault data online. Phan Cự Tiến (chủ biên), 1988: Bản đồ địa chất Campuchia, Lào và Việt Nam 1: 1 000 000. Tổng cục Địa chất Hà Nội - Việt Nam. Bùi Văn Thơm, 2001: Đặc điểm hoạt động Tân kiến tạo đới đứt gãy Đakrông - Huế. TC Địa chất, số 267, 64-75. Bùi Văn Thơm, 2002: Một số đặc điểm đứt gãy Tân kiến tạo khu vực Bắc Trung bộ. Luận án Tiến sỹ. Viện Địa chất. Cao Đình Triều, 2010: Seismic hazads in Vietnam. S&T Publ. House-Hanoi. Lê Thạc Xính (chủ biên), 1969: Bản đồ địa chất Lào 1: 500 000. Cục Địa chất Lào - Vientiane. Nguyễn Đình Xuyên (chủ nhiệm), 1985: Động đất trên lãnh thổ Việt Nam. Lưu trữ tại Viện khoa học Việt Nam, Hà Nội. Nguyễn Trọng Yêm (chủ nhiệm), 2005: Nghiên cứu thiên tai nứt đất lãnh thổ Việt Nam và các giải pháp phòng tránh, giảm nhẹ thiệt hại - Đề tài điều tra cơ bản. Lưu trữ tại Viện Địa chất.